PENGARUH MOTIVASI KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. TRI INDO GLOBAL - Kharisma Refani; Siwi Nur Indriyani (Jurnal Manajemen Bisnis Krisnadwipayana, 2024)
To analyze the influence of work motivation and organizational commitment on employee work productivity at PT. Tri Indo Global. This research is included in the category of causal associative research using a quantitative approach. The sampling technique used a saturated sample. All members of the population were sample.. The analytical method uses simultaneous and partially linear regression analysis. The results showed that in simultaneous or partially ways the work motivation and organizational commitment on employee work productivity at PT. Tri Indo Global.